PENGEMBANGAN MEDIA UNO STACKO CHEMISTRY PADA MATERI HIDROKARBON - Amelia Mayang Sari Vinanda; Eny Enawaty; Husna Amalya Melati (Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of this research was to find out the feasibility and teachers’ responses toward the development of Uno Stacko Chemistry (Uno Stachem) media. The type of this research was Research and Development (R&D) based on ADDIE development model. Uno Stachem media as the research subject was tested by chemistry teachers from three different schools. The instruments used on collecting data were the evaluation sheets of feasibility (media, material, and language) and teachers’ responses questionnaires through indirect communication technique. The data were analyzed by using qualitative descriptive technique. It revealed that the results of data analysis based on the evaluation of media, material, and language feasibility were 100%, 94%, and 83% respectively with a very practical category. Based on the teachers’ responses questionnaires result, Uno Stachem media receive a very good response with the percentage of 89%. Therefore, Uno Stachem learning media is very feasible to support chemistry learning on hydrocarbon material.